Modern Operator Theory and Applications The Igor Borisovich Simonenko Anniversary Volume - Erusalimskii, Yakob M.; Gohberg, Israel; Grudsky, Sergei M.; Rabinovich, Vladimir; Vasilevski, Nikolai (Operator Theory: Advances and Applications, 2007)
This volume is dedicated to the eminent Russian mathematician Igor Borisovich Simonenko on the occasion of his 70th birthday. It consists of a selection of 15 original contributions written by leading experts in operator theory. The topics reflect the wide range and the rich variety of areas of interests, achievements and influence of I.B. Simonenko. The book also includes his biography, the complete list of publications and a list of his Ph.D. students. Among the topics covered are functional, Toeplitz and Toeplitz plus Hankel, local and nonlocal, singular integral and convolution operators, and continuous analogs of resultant operators. The contributions analyze and solve problems of factorization, irreducibility, asymptotics of determinants, finite sections, and index problems for different types of operators. Applications concern problems in financial mathematics and hydrodynamics. The book will be of interest to a wide audience of pure and applied mathematicians.